The impact of translation on risk management in oil and gas projects in Iraq - Obaid, Ali Bashar; Hadina Habil (Penerbit Universiti Kebangsaan Malaysia, 2025)
Oil and gas pipelines (OGPs) are an essential yet controversial infrastructure for transporting petroleum products due to their exposure to various natural and manmade hazards. This paper examines the critical risk factors (CRFs) associated with OGPs and the role translation plays in risk management within the oil and gas sector, particularly in Iraq. Utilizing a survey conducted through postal questionnaires, the study identified fourteen primary CRFs related to accidents in OGP projects, comparing risk significance across various countries in Asia, Europe, the Middle East, and North Africa. The findings revealed significant discrepancies in CRFs influenced by geography and culture, emphasizing the need for improved risk management strategies. In Iraq, translation issues hamper effective communication among diverse stakeholders in oil and gas projects, leading to misunderstandings and costly mistakes. The unique characteristics of Iraq's oil and gas industry, established under a service contract model, necessitate high-quality translation of contracts and risk management documents. Specific findings highlight instances where translation inaccuracies have resulted in project delays and financial losses, underscoring the impact of linguistic and cultural complexities on risk management. This study highlights the inherent risks in translating technical documents and reinforces the critical need for skillful translation practices. By providing guidance for robust translation strategies, the findings aim to enhance risk management practices related to OGPs, thereby fostering greater efficiency and safety in the industry, particularly in developing nations like Iraq. The paper outlines key themes, such as the analysis of geographical and cultural influences on CRFs and proposed strategies for improving translation accuracy, offering a comprehensive roadmap for readers.